Characterisation of thin walled sandwich structures comprising steel hollow spheres for the core - Yiatros, Stylianos; Marangos, Orestes; Brennan, Feargal P. (My University, 2019)
Steel hollow sphere assemblies are a special type of metal foams that can offer low weight, energy dissipation and ductility [1, 2]. The composite manufactured using thermosetting epoxies can be attractive as core in hollow sections and sandwich configurations, ameliorating shortcomings of precursor powder metallurgy, such as more uniform cell size as well as lower cost and better tensile responses compared to sintered assemblies [3]. The work herein describes the design and mechanical testing of steel foam-epoxy composites to estimate the static and cyclic properties of these composites. This included static properties in compression of sphere assemblies, including the crushing propagation [4]. 4-point bending tests were utilized to capture shear modulus and shear strength in the sphere assembly core, sandwiched by two steel plates. Two types of sphere assembly sandwich cores were tested, the first one being 3 layers of 4.5 mm diameter spheres(referred to as ‘SFS4’) and the second 4 layers of 2.3 mm spheres and 1 layer of 4.5 spheres in the middle (referred to as ‘SFSGRD’), in order to quantify any potential gains in shear strength with limited increase in core density near the face plates. For all static tests, Digital Image Correlation techniques were used to capture surface displacements in the specimens, providing a richer data set for the evolution of the responses. Fatigue tests in 4-point bending followed, for the two types of sandwich specimens in order to quantify the cycles to failure for the two types as well as the residual stress in the specimens, after the failure had occurred. The fatigue tests also included the testing of aged specimens, which were dipped in north sea saline conditions for 15 days, in order to quantify the effect corrosion on exposed sandwich specimens. All in all, more than 100 specimens were used in this study and the data has provided insights in the response of these cellular assemblies as core in sandwich configurations in static and cyclic conditions, which is useful in defining potential multifunctional applications for such structures. References [1] J. Banhart. Manufacture, characterisation and application of cellular metals and metal foams. Progress in Material Science 2001, 46( 6): 559-632. [2] B. Smith, S. Szyniszewski, J. Hajjar, B. Schafer, S. Arwade. Steel foam for structures: a review of applications, manufacturing and material properties. Journal of Constructional Steel Research 2012, 71:1-10. [3] S. Szyniszewski, B. Smith, J. Hajjar, B. Schafer, S. Arwade. The mechanical properties and modelling of sintered hollow sphere steel foam. Materials & Design 2014, 54:1083-1094. [4] S. Yiatros, O. Marangos, R. A. Votsis, F. P. Brennan. Compressive properties of granular foams of adhesively bonded steel hollow spheres. Mechanics Research Communications 2018, 94: 13-20.